Examining Used and Sportswear Supply Chain Strategy and Indicators - Maklári, Gergely; Sipos, Csanád (International Journal of Engineering and Management Sciences, 2021)
The following study presents the supply chain strategy of a second-hand and sportswear company in Hungary. The study discusses the main tasks of supply logistics, the level of logistics service, the main determining elements of the level of logistics service, and the measurement of customer satisfaction. From the first step of the process, we can fully follow the processes until the last activity. We can learn in detail about the sub-processes, such as: types of clothing collection, sourcing, warehousing, selection, disassembly, processing, receipt of goods and sales. The aim of the study is to make the processes more transparent for everyone.